Bebidas funcionais fermentadas de cascas de frutas ricas em compostos antioxidantes - Coutinho, Lairy Silva (2019)
There are fruit peels rich in bioactive compounds that are interesting to consumption, but often agroindustry does not take advantage of these co-products in the development of new products with greater functionality that can generate health benefits; soon this work aimed to elaborate fermented alcoholic beverages from fruit peels, to evaluate the fermentation kinetics of the musts, physical-chemical characteristics and bioactive compounds present in the elaborated beverages. All musts (with and without mixing processes containing: grape peel, blueberry husk, jabuticaba peel, pineapple peel and cane juice) were standardized for the initial soluble solids contents at 20 ° Brix, yeast was used Sacharomyces Cereviseae Blastosel MV, BOD at 28 ° C and after fermentation and finishing of the fermented alcoholic beverages, they were submitted to physical and chemical analyzes, such as: acidity, anthocyanins, total phenolic compounds, antioxidant activity, chromatographic quantification organic acids, sugars and alcohols), as well as instrumental color analysis. The statistical parameters used were analysis of variance, Tukey's test and design of mixtures. The main results of the beverages without blending processes were related to the beverages obtained from red fruit peels (grape, jaboticaba and blueberry peels), since some bioactive compounds found (gallic acid, caffeic acid, total phenolic compounds) were higher than in literature on red wine beverages; as well as the beverages of the mix designs, it was observed in the general context greater influence of red fruit peels used in the evaluated bioactive compounds and the beverages of greater desirability with respect to the bioactive compounds, ethanol content and chromaticity parameters were the beverages containing intermediate amounts between the mixing components. The fermentation kinetics of all musts were satisfactory for the production of fermented alcoholic beverages; As for the physical parameters, purple-red tint was observed in beverages with intermediate concentrations of grape, blueberry and jaboticaba peel; as for the alcohol content of the beverages in general, all obtained a satisfactory characteristic for the type of drink obtained and the beverages of greatest desirability among all the mix designs analyzed was referring to the central points (with intermediate concentration between the mixing components). It is therefore possible to conclude that the beverages obtained from the evaluated fruit peels had satisfactory physical and chemical characteristics to elaborate the development of new products from agroindustrial co-products and have functional characteristics due to the bioactive compounds found in most elaborated beverages.